Area handbook for Libya - United States. Department of the Army.; Stanford Research Institute; American University (Washington, D.C.). Foreign Area Studies (Washington, D.C. : For sale by the Supetintehdent of Documents, U.S. Government Printing Office, 1969)
"This volume is one of a series of handbooks prepared under the auspices of Foreign Area Studies (FAS) of The American University, designed to be useful to military and other personnel who need a convenient compilation of basic facts about the social, economic, political, and military institutions and practices of various countries"--Page ii.
"Research and writing were completed on June 1, 1969."
Includes bibliographical references (pages 281-296) and index.
Keywords: Social conditions; Politics and government; Economic history; Libya -- Politics and government; Libya -- Economic conditions; Libya -- Social conditions; Libye; Libye -- Politique et gouvernement; Libya; Handbooks and manuals